The global energy crisis as an opportunity - Restrepo López, Natalia (Cuadernos de Administración, 2022)
The world is presently facing its first global energy crisis. While for several years, the attention paid to the behavior of global energy markets has been growing, as have questions relating to their impact on carbon emissions and the need to diversify countries’ energy production matrix, the ongoing war between Russia and Ukraine has exacerbated the urgency of finding sustainable answers to these questions. Russia has been one of the world’s largest exporters of fossil fuels, and its recent supply-related decisions have pushed prices up, especially gas prices. The costs associated with gas and coal account for about 90% of electricity generation costs worldwide. This has raised previous inflationary pressures, increased food insecurity risks in emerging countries, and accelerated the coming recession. For the first time, the current challenging context has led economic and climate priorities to become aligned and highlighted the fundamental role of governmental decisions in achieving the energy transition. Among the crucial challenges to achieving this objective is the attainment of the necessary funds (investments) to complete the transition and the transformation of the export matrix, especially in countries where fossil fuels hold a preponderant position in this matrix. The latter is in order to ensure an energy transition that does not compromise macroeconomic stability. This crisis constitutes a turning point in global dynamics, hopefully leading to a successful, sustainable, and just energy transition. Issue Overview Issue 74 of the Cuadernos de Administración journal falls within the September - December 2022 quarter. The ten papers published in this issue result from the journal’s commitment to maintaining a permanent call for pieces to encourage continuous scientific dissemination, maintaining the highest quality standards. This issue has seen participation by authors from several countries and regions of Colombia, who submitted their manuscripts to our editorial process. The journal and its editorial committee would like to thank our reviewers, whose experience and knowledge helped us through the evaluation of each paper. The nine published articles result from exhaustive research processes aimed at solving questions associated with various aspects of the administrative and organizational sciences. The first one, entitled “Consumption habits and e-commerce among millennials in metropolitan Lima during the Covid-19 pandemic,” develops a non-experimental design with a quantitative and correlational approach to determine whether consumption habits are related to e-commerce among millennials. The paper frames its study sample in Lima, Peru, during the Covid-19 pandemic. “Emotional labor in the service sector: the role of organizational commitment” analyzes the level of organizational commitment and emotional labor behaviors of employees in the service sector. Additionally, it seeks to determine a significant relationship between these variables through statistical and econometric analysis based on 433 surveys of service sector workers in the Zonguldak province of Turkey. The authors find a meaningful relationship between emotional labor and organizational commitment’s normative and emotional dimensions. The third paper in this issue is entitled “Effects of the strategic framework on business competitiveness: an empirical study .”This paper discusses the practical usefulness of mission and vision statements in a business setting by evaluating the relationship between these elements and the achievement of results, specifically in terms of competitiveness. This relationship is studied through an empirical partial least squares structural equation model estimated from a sample of 120 large companies registered in the Department of Santander, Colombia. Later in our issue, we find “Knowledge management in Colombian companies following the Nonaka and Takeuchi Model: a study of multiple intertwined cases.” The objective of this study is to determine the level of knowledge management through the three components of Nonaka Takeuchi’s theory, based on ten multiple intertwined case studies in five large companies and five Colombian SMEs. Through analysis, the authors show that, in all four ways of converting knowledge from tacit to explicit, the five SMEs scored higher than the five large companies. The results also account for knowledge management activities in the ten cases, which are necessary so that the knowledge created will stay strong. “Value-added from the productive efficiency of intellectual capital in large agroindustrial companies” proposes implementing the Value Added Intellectual Coefficient (VAIC) as a measure of value-added creation from the productive efficiency of intellectual capital in large agroindustrial companies in the department of Magdalena, Colombia. Based on value-added statements, multiple linear regression models, and panel data, the authors found that most companies analyzed scored well in value-added creation. This last paper is followed by “Analysis of Saber Pro tests in business administration programs in Colombia between 2016 and 2020,” which analyzes the Saber Pro tests of Business Administration programs in Colombia through a descriptive study with a quantitative approach. Based on ICFES-published information, the authors found that citizenship skills, written communication, and quantitative reasoning scored the lowest results as concerns generic competencies. On the other hand, regarding specific competencies, the lowest-performing outcomes were in financial and organizational management. “Gender gap analysis of the unemployment rate in Colombia: 2001-2021.” This paper seeks to model the evolution of the unemployment gap in Colombia during the period 2001:01 - 2021:06 to forecast its behavior and determine volatility. For this purpose, the authors implement a Seasonal Autoregressive Integrated Moving Average Model (SARIMA) with Generalized Autoregressive Conditional Heteroscedasticity (GARCH). According to their estimates, the authors conclude that, although the gender gap showed a slight decrease in the last two decades, it was negatively impacted by the Covid-19 pandemic, which led to an increasing behavior. Additionally, the series volatility increases, making it more vulnerable to economic and seasonal cycles. “Human resource management model from the perspective of internal social responsibility in medium and large companies in Ibagué” presents a human resources management model from the perspective of social responsibility for medium and large companies in Ibagué, Tolima, Colombia. For this purpose, the authors conducted quantitative research with a correlational and explanatory approach based on Factor Analysis (FA) and Structural Equations (SEM) techniques. Estimates suggest that the human resource management model from the perspective of internal social responsibility should consider the following variables: quality of life at work, promotion of formal university education, investment in training, development, and welfare of human talent, and professional promotion of employees, among others. Our issue ends with a thought-provoking article entitled “Worker well-being, effective strategies from positive organizations,” which theoretically describes the pillars that the literature has identified as crucial for an organization to be positive and demonstrate its concern for the well-being of its workers. The study proposes four elements: the implementation of healthy organizational practices to contribute to the well-being of employees; a focus on positive leadership involving feedback, communication, and goal setting; positive environments for workers; and meaningful work. The publication of issue number 74 of Cuadernos de Administración of the Universidad del Valle’s Faculty of Management is a step towards consolidating ourselves as a prestigious journal in the scientific dissemination of knowledge in various fields of managmente and organizational sciences. We want to thank each of the authors and peer reviewers who supported the editorial process and stress that the content of each paper is the responsibility of its authors.